Moderating effect of gender on the associations of perceived attributes of the neighbourhood environment and social norms on transport cycling behaviours. (June 2019) - Bourke, Matthew; Craike, Melinda; Hilland, Toni A.
Abstract: Introduction: Cycling for transport has various health benefits. However, in Australia, commuter cycling rates are low, especially among women. Despite this, little is known about the factors that may explain why women cycle for transport less than men. This study aimed to examine whether components of the neighbourhood built environment and social norms were associated with transport cycling differently in men and women. Methods: This cross-sectional study recruited participants from organisations with bicycle user groups in Melbourne, Australia. An online questionnaire measured participant's (n = 228) perceptions about cycling infrastructure and cycling convenience in their neighbourhood, and descriptive and injunctive norms towards cycling. Logistic regression models were run to test the main effects of gender and participant's perceptions of each of these factors on transport cycling. The moderating effect of gender was tested by adding an interaction term between gender and each of the neighbourhood built environment and social norm variables into the main effects model. Results: Results showed that women were significantly less likely to cycle for transport, while participants who reported positive perceptions of neighbourhood cycling convenience and descriptive norms were significantly more likely to cycle for transport in the previous week. Gender moderated the association between neighbourhood cycling convenience and cycling for transport whereby the association was only significantly positive in women. Conclusion: Results from this study suggest that to increase rates of transport cycling in women it may be necessary to increase the convenience of cycling in neighbourhoods for multiple purposes, such as going to the shops, running errands, or escorting children. Additionally, improving social norms towards cycling may increase rates of commuter cycling in both men and women. Highlights: Examined gender moderated correlates of transport cycling. Perceived neighbourhood cycling convenience is related to transport cycling in women. Perceived descriptive norms related to transport cycling in men and women. Policies should target improvements in neighbourhood cycling convenience.